AI-Generated Instructional Animation for Local Cultural Literacy: A Design and Development Study in Indonesian Islamic Secondary Education - Nurhasanah Nurhasanah; Nurlina Sjahrir; Johar Linda (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Global digital penetration has intensified a cultural literacy deficit among adolescents, including Indonesian Islamic secondary school (Madrasah Aliyah) students who increasingly engage with globalized content at the expense of indigenous heritage. This study developed and evaluated an AI-generated animation video focusing on the Karampuang Traditional House to strengthen local cultural literacy at Madrasah Aliyah Negeri (MAN) 1 Sinjai, South Sulawesi. Utilizing a Research and Development (R&D) framework, this study integrated the ADDIE model and the Multimedia Development Process (MDP). Evaluation involved expert validation from multimedia technology and cultural heritage specialists, followed by a school-based implementation trial with 104 students. Data were gathered using structured Guttman-scale questionnaires assessing perceived educational usefulness and visual attractiveness. Content expert validation yielded a perfect feasibility score of 100%, whereas media expert validation reached 83.3%, requiring minor visual refinement. Field testing revealed that 92.3% of students rated the tool as